A note on the population genetic consequences of delayed larval development in insects - Salles,Marcos Mattoso de (2013)
Observations by Dobzhansky's group in the 1940s suggesting that the presence of recessive genotypes could account for lower larval developmental rates in Drosophila melanogaster were not confirmed at the time and all subsequent investigations on this subject focused on the analysis of ecological models based on competition among pre-adult individuals. However, a paper published in this journal in 1991 eventually confirmed the finding made by Dobzhansky and his co-workers. In this report, we provide a theoretical analysis of the population genetic effects of a delay in the rate of larval development produced by such a genetic mechanism.